STRATEGI BRANDING DAN PENCATATAN KEUANGAN SEDERHANA UNTUK MENINGKATKAN DAYA SAING UMKM DESA CINTAWARGI - Rohma Septiawati; Meliana Puspitasari; Mumun Maemunah; Citra Savitri; Moch Agus Ariffianto; Rivan Wibowo (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to improve the competitiveness of MSMEs in Cintawargi Village through the implementation of appropriate branding strategies and simple financial record-keeping. The background of this study stems from the phenomenon of low branding literacy and the limited awareness among MSME actors regarding the importance of simple bookkeeping as a basis for business decision-making. The implementation method involved mentoring, training, and direct application with partner MSMEs. The results of the study show an improvement in understanding of digital branding, the implementation of simple record-keeping, and improvements in financial management that support competitiveness. The recommendations emphasize the importance of continuous support from local government and academics in assisting MSMEs